2008
DOI: 10.7577/nbf.240
|View full text |Cite
|
Sign up to set email alerts
|

Från görande till lärande och förståelse; En studie av lärares lärande inom estetik

Abstract: The aim of this article is to analyse teachers' changing ways of talking about children's aesthetic learning in the early years as a result of a research and development project. With a point of departure in developmental and variation theory, a praxis oriented project was designed with the aim of finding out whether collaborative talk and meta-cognitive dialogues could contribute to children's learning of music, dance and poetry. The participating teachers were offered in-service training in order to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 5 publications
0
8
0
8
Order By: Relevance
“…Abstracts and titles screened n=1551 in Swedish (Asplund Carlsson et al, 2008;R€ onnerman, 2008) and the remaining three in Dutch (Peeters, 1993), German (Richter, 2012) and Slovenian (Vonta et al, 2007). We involved country experts in data extraction that was relevant for the in-depth review.…”
Section: Screening By National Expertsmentioning
confidence: 99%
“…Abstracts and titles screened n=1551 in Swedish (Asplund Carlsson et al, 2008;R€ onnerman, 2008) and the remaining three in Dutch (Peeters, 1993), German (Richter, 2012) and Slovenian (Vonta et al, 2007). We involved country experts in data extraction that was relevant for the in-depth review.…”
Section: Screening By National Expertsmentioning
confidence: 99%
“…However, there are studies showing that teachers' content knowledge in music do have positive effects on practice. That the teachers reflect on the importance of music in itself can be regarded as important in order to focusing children's ability to develop musical knowledge and making musical experiences (Asplund Carlsson et al, 2008;Still, 2011). Teachers in early childhood education also need insight into the development of a child's singing voice, and knowledge about what keys can fit children's developing voices (McAllister & Södersten, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…In preschool and primary school, it has been shown that many musical activities are enacted without teachers reflecting about the content and without considerations of the pedagogy being used (Asplund Carlsson, Pramling, & Pramling Samuelsson, 2008;Still, 2011). However, there are studies showing that teachers' content knowledge in music do have positive effects on practice.…”
Section: Introductionmentioning
confidence: 99%
“…Pang and Marton (2003) described variation theory as the theoretical underpinning of the learning study approach, and the socalled object of learning is of vital importance in this theory (Pang and Marton 2005). It is important to clearly specify the object of learning (Asplund Carlsson et al 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%